ANALISIS PERBANDINGAN MOVING AVERAGE, EXPONENTIAL SMOOTHING, DAN TREND PROYECTION PADA PERAMALAN PRODUKSI CRUDE PALM OIL PT. EKADURA INDONESIA - Purwanto Deka; Machasin Machasin; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Forecasting is the art and science of predicting future events using data from the past. This research was conducted at PT. Ekadura Indonesia which aims to find out how to calculate the correct and effective production forecasting and to find out the most suitable forecasting method for the production of crude palm oil PT. Ekadura Indonesia. This research is a quantitative descriptive study, the analysis used in this study includes the method of moving average, exponential smoothing, and trend projectionby comparing the forecasting error rate measured from the smallest mean absolute percentage error. The result of this study indicate that of the three methods used, the projection trend methods have the smallest mean absolute percentage error, which is 2,1023%.Keyword: Forecasting, Moving Average, Exponential Smoothing, Trend Projection, and MAPE.